2015
DOI: 10.1080/02791072.2015.1031412
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana Use, Motives, and Change Intentions in Adolescents

Abstract: Research typically focuses on motives to use or abstain from marijuana (MJ) in isolation; few studies have integrated both constructs in models of MJ use decision making. We expand the existing literature by integrating these motives in cognitive models of use and cessation in adolescents. We expected use motives to account for past use and intentions for future use, and for motives to abstain to dominate models explaining intention, desire, and self-efficacy for quitting. Adolescent MJ users (N = 162) reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Contrary to expectation, enhancement and expansion motives (but not coping motives) were related to post-infraction use. This is consistent with prior work finding enhancement and expansion (but not coping) motives were positively related to intention to use cannabis among adolescents (Dash & Anderson, 2015). Taken together, these data suggest that enhancement and expansion motives may play important roles in continued cannabis use, especially following university sanctions.…”
Section: Discussionsupporting
confidence: 92%
“…Contrary to expectation, enhancement and expansion motives (but not coping motives) were related to post-infraction use. This is consistent with prior work finding enhancement and expansion (but not coping) motives were positively related to intention to use cannabis among adolescents (Dash & Anderson, 2015). Taken together, these data suggest that enhancement and expansion motives may play important roles in continued cannabis use, especially following university sanctions.…”
Section: Discussionsupporting
confidence: 92%
“…For example, one study of adolescents found that common motives for marijuana use included wanting to have a good time with friends, boredom, a desire to relax, and seeking insight (Patrick et al 2011). Another study found that adolescent marijuana users reported using because they wanted to fit in with a social group, avoid social rejection, relieve pain, and reduce stress (Dash & Anderson 2015). Furthermore, teens have been found to use marijuana in order to facilitate group interactions (Anderson; Sitney & White 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The demographics and motives for use among plant medicine users in these studies stand in contrast to some national studies of recreational drug use which suggest that people who use illegal drugs in the US are more likely to be in their teens and 20s, racial/ethnic minorities, have lower educational attainment than non-drug users (Samhsa, 2013). Likewise, drug use is generally hypothesized to be motivated by the desire for euphoria/mood alteration, enhanced sexuality and physical performance, social facilitation, social conformity/peer pressure, boredom, habit, and self-insight (Dash, 2015; Nicholson et al, 2002; Riley & Blackman, 2009; Solowji et al, 1992; Ter Bogt et al, 2005). Ray and Ksir summarized the main motivators for illegal drug use as pain reduction and pleasure enhancement (1993), a finding not supported by this study.…”
Section: Discussionmentioning
confidence: 99%